Efeitos da dor muscular tardia no triceps sural induzida pelo exercício sobre o controle da estabilidade em diferentes posturas - (:unkn) unknown (Universidade Federal do Pampa, 2023)
A common strategy to manipulate exercise intensity for strength gains is to select exercises requiring eccentric muscle actions. These exercises are common, for example, for the training and rehabilitation of the triceps surae muscles. However, this context is also known to cause delayed onset muscle soreness (DOMS). DOMS in the triceps sural can have negative repercussions on the performance of daily life tasks. Although the acute effects of triceps sural fatigue are addressed in previous studies, there is still little evidence on the effects of triceps sural DOMS on postural control. In this study, we determined whether triceps sural DOMS affects stability in unipedal bipedal postural control tasks. Participate in this study 24 subjects with (mean ± standard deviation) age of 23.8 ± 3.69 years, body mass of 68.65 ± 12.67 kg, and height of 1.69 ± 0.08 m, assessed on two days. On the first day, demographic data were collected, and the presence of triceps sural pain (through a numerical scale and pressure pain threshold), and postural control during bipedal and unipedal standing and unipedal landing tasks (through a force platform and calculation of the center of pressure and stabilization time) were assessed. Next, they completed a protocol to induce DOMS in the triceps sural (heel raise exercise to exhaustion). On the second day, 48 h after DOMS induction, DOMS was assessed using the numerical scale and pressure pain threshold and postural control during standing and landing tasks. DOMS and postural control results were compared between days. DOMS in the triceps sural was observed 48 h after its induction and led to increased mediolateral displacement of the center of pressure in standing postural control tasks. However, the presence of DOMS did not seem to induce differences in time to stabilization in unilateral landing tasks. In conclusion, exerciseinduced muscle soreness in the triceps sural led to impaired control of the mediolateral component of the center of pressure during postural tasks. This highlights the importance of evaluating and adapting training and rehabilitation sessions, considering individual differences in task difficulty and strategies used by participants for posture control.
Effects of triceps surae exercise-induced delayed onset muscle soreness on control of body stability in different postures
Keywords: Postural control; Fatigue; Muscle pain; Stability; Controle postural; Fadiga; Dor muscular; Estabilidade; CNPQ::CIENCIAS DA SAUDE